Rodzinna hipercholesterolemia. Badanie kliniczne kluczem do sukcesu diagnostycznego - Dewan, Pooja; Grover, Chander (Pediatric Endocrinology Diabetes and Metabolism, 2021)
Familial hypercholesterolemia is a rare genetic disease, although it is amongst the commonest dyslipidemias. It characterized by raised cholesterol levels and normal triglyceride levels. Childhood presentation of familial hypercholesterolemia can cause early atherosclerotic plaque deposition in arteries and a markedly increased risk of coronary heart disease (CHD) at a young age. A thorough clinical examination, including identification of signs like cutaneous lesions and careful eye examination, can clinch the diagnosis.